2021
DOI: 10.1021/jacs.1c05793
|View full text |Cite
|
Sign up to set email alerts
|

Null Exciton-Coupled Chromophoric Dimer Exhibits Symmetry-Breaking Charge Separation

Abstract: A comprehensive understanding of the structure− property relationships in multichromophoric architectures has pushed the limits for developing robust photosynthetic mimics and molecular photovoltaics. The elusive phenomenon of null exciton splitting has gathered immense attention in recent years owing to the occurrence in unique chromophoric architectures and consequent emergent properties. Herein, we unveil the hitherto unobserved null exciton coupling assisted highly efficient photoinduced symmetry-breaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(146 citation statements)
references
References 103 publications
8
138
0
Order By: Relevance
“…It has been found that the SB-CS rate and the recombination rate is strongly sensitive to the electronic coupling between the adjacent molecular units that is determined by the relative inter-/intra-molecular distance and orientation. 13,18–21 For example, Wasielewski group investigated the SB-CS process in cofacial and linear perylene diimide (PDI) dimers and found that ultrafast SB-CS (1/0.52 ps −1 ) could be conducted in cofacial PDI dimer even in weakly polar toluene but with a fast recombination rate (1/222 ps −1 ). 22 Instead, SB-CS cannot proceed in linear PDI dimer in toluene but only in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the SB-CS rate and the recombination rate is strongly sensitive to the electronic coupling between the adjacent molecular units that is determined by the relative inter-/intra-molecular distance and orientation. 13,18–21 For example, Wasielewski group investigated the SB-CS process in cofacial and linear perylene diimide (PDI) dimers and found that ultrafast SB-CS (1/0.52 ps −1 ) could be conducted in cofacial PDI dimer even in weakly polar toluene but with a fast recombination rate (1/222 ps −1 ). 22 Instead, SB-CS cannot proceed in linear PDI dimer in toluene but only in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The negative signal centered at 458 nm is ascribed to the superposition of stimulated emission signal with ESA ( Figure 2 ). During the entire delay time, the curve shape of ESA remains the same with a time depend decay of OD, indicating that the ESA originates from an excited singlet state and there is no additional transition process In addition, the decay of extracted dynamics traces at 458 nm is similar to that at 662 nm ( Figure S1 ), suggesting that the ESA is derived from the fluorescent states and there is no additional transition process occurring [ 33 , 34 , 35 ]. This ESA behavior is appreciated in ultrafast OL.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, the interference between vibronic couplings described here is not phase dependent and always leads to larger overall couplings. This is distinctly different, for example, from the case of null excitons 44 where charge-transfer and Coulomb couplings can interfere destructively. The phase-independent interference between vibronic couplings manifests in more general contexts.…”
Section: Interference Between Vibronic Couplingsmentioning
confidence: 83%